Differential impact of resilience on demoralization and depression in Parkinson disease - de Figueiredo, John M.; Zhu, Boheng; Patel, Amar S.; Kohn, Robert; Koo, Brian B.; Louis, Elan D. (Frontiers in Psychiatry, 2023)
Objectives: The objective of this study was to study the interrelations of demoralization, depression, and resilience in patients with Parkinson disease, and, more specifically, to determine if higher resilience in patients with Parkinson disease is associated with lower demoralization, lower depression, or both.Methods: Outpatients with Parkinson disease (N=95) were assessed for demoralization, depression, and resilience, as well as sociodemographic, clinical, and treatment-related variables. Bivariable associations, standard regressions, linear regression with copula correction, and correspondence analysis were used to analyze the data.Results: Although the bivariable association between resilience and depression was statistically significant, the association ceased to be significant when demoralization was taken into consideration in both standard regressions and linear regression with copula correction. By contrast, the association between resilience and demoralization was significant when depression was not taken into consideration and continued to be significant when depression was taken into consideration.Correspondence analysis revealed that low resilience was strongly related to demoralization combined with depression, whereas normal resilience was closely correlated with depression without demoralization.